2010
DOI: 10.1038/mt.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Toward Gene Therapy for Cystic Fibrosis Using a Lentivirus Pseudotyped With Sendai Virus Envelopes

Abstract: Gene therapy for cystic fibrosis (CF) is making encouraging progress into clinical trials. However, further improvements in transduction efficiency are desired. To develop a novel gene transfer vector that is improved and truly effective for CF gene therapy, a simian immunodeficiency virus (SIV) was pseudotyped with envelope proteins from Sendai virus (SeV), which is known to efficiently transduce unconditioned airway epithelial cells from the apical side. This novel vector was evaluated in mice in vivo and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 43 publications
6
116
0
Order By: Relevance
“…We have, therefore, recently pseudotyped a simian lentiviral vector with the SeV F and HN proteins (F/HN-SIV) 23 and have shown that the virus efficiently transfects mouse airway epithelium in vivo, as well as human air-liquid interface cultures. 24 Moreover, F/HN-SIV-mediated gene expression persists for more than 17 months after a single administration and repeated administration (3 doses) is feasible. 24 It is interesting that the HN-mediated activation of NK cells does not appear to interfere with F/HN-SIV-mediated gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have, therefore, recently pseudotyped a simian lentiviral vector with the SeV F and HN proteins (F/HN-SIV) 23 and have shown that the virus efficiently transfects mouse airway epithelium in vivo, as well as human air-liquid interface cultures. 24 Moreover, F/HN-SIV-mediated gene expression persists for more than 17 months after a single administration and repeated administration (3 doses) is feasible. 24 It is interesting that the HN-mediated activation of NK cells does not appear to interfere with F/HN-SIV-mediated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, F/HN-SIV-mediated gene expression persists for more than 17 months after a single administration and repeated administration (3 doses) is feasible. 24 It is interesting that the HN-mediated activation of NK cells does not appear to interfere with F/HN-SIV-mediated gene expression. The F/HN-SIV vector may, therefore, be ideally suited for pulmonary gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This method now enables the rational design of more effective delivery procedures in the airway gene transfer protocols used in normal and CF mouse models. 1,2,14,15 It should also permit improvements in reliability and repeatability to boost outcome effectiveness, reduce outcome variability, and decrease the volumes of costly gene vectors needed in mouse model studies.…”
Section: Introductionmentioning
confidence: 99%
“…7 The trial reached its primary endpoint (change in lung function as measured by forced expiratory volume (FEV 1 ) comparing active and placebo (3.7%, Cystic Fibrosis Gene Therapy of persistent expression and efficacy upon repeated administration and are log orders more efficient than the best non-viral formulation. [8][9] Lentiviral vectors have been pseudotyped with various envelope proteins to enable transduction of airway epithelial cells. [8][9] A lentiviral vector pseudotyped with the F and HN proteins from Sendai virus, which has a natural tropism for the airways, is furthest advanced along a translational research path and a first-in-man trial will commence in late 2017.…”
mentioning
confidence: 99%
“…[8][9] Lentiviral vectors have been pseudotyped with various envelope proteins to enable transduction of airway epithelial cells. [8][9] A lentiviral vector pseudotyped with the F and HN proteins from Sendai virus, which has a natural tropism for the airways, is furthest advanced along a translational research path and a first-in-man trial will commence in late 2017.…”
mentioning
confidence: 99%